2019
DOI: 10.3390/ijms20174238
|View full text |Cite
|
Sign up to set email alerts
|

Cafestol and Kahweol: A Review on Their Bioactivities and Pharmacological Properties

Abstract: Cafestol and kahweol are natural diterpenes extracted from coffee beans. In addition to the effect of raising serum lipid, in vitro and in vivo experimental results have revealed that the two diterpenes demonstrate multiple potential pharmacological actions such as anti-inflammation, hepatoprotective, anti-cancer, anti-diabetic, and anti-osteoclastogenesis activities. The most relevant mechanisms involved are down-regulating inflammation mediators, increasing glutathione (GSH), inducing apoptosis of tumor cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
91
0
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 135 publications
(98 citation statements)
references
References 93 publications
1
91
0
6
Order By: Relevance
“…Cafestol and kahweol are mainly present as fatty esters in unfiltered coffee, and are both found in low concentrations in the filtered preparation. Filtered coffee is the most widely consumed form in Central Europe and the United States [ 20 ]. Despite that, a clinical trial found that paper-filtered coffee protects humans against oxidative DNA damage [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cafestol and kahweol are mainly present as fatty esters in unfiltered coffee, and are both found in low concentrations in the filtered preparation. Filtered coffee is the most widely consumed form in Central Europe and the United States [ 20 ]. Despite that, a clinical trial found that paper-filtered coffee protects humans against oxidative DNA damage [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…The purine alkaloid caffeine and chlorogenic acids are considered the main bioactive compounds of coffee, along with cafestol and kahweol pentacyclic diterpenes, trigonelline and melanoidins [35,36]. Thus, besides phytocannabinoids, their content in investigated hemp coffee was also investigated.…”
Section: Caffeine and Chlorogenic Acids Contentmentioning
confidence: 99%
“…Kahweol is a natural diterpene extracted from coffee beans that has antioxidant effects in the liver [16]. Specifically, kahweol regulates intracellular levels of ROS by increasing Nrf2 expression [21,33].…”
Section: Discussionmentioning
confidence: 99%